Purpose, Pedagogy and Philosophy: “Being” an Online Lecturer - Coker, Helen (International Review of Research in Open and Distributed Learning, 2018)
Instructing online has become an increasingly common aspect of a university lecturer’s role. While research has developed an understanding of the student learning experience, less attention has been paid to the role of the lecturer. This study observed the practice of university lecturers teaching in a range of undergraduate degree programmes in the United Kingdom. The lecturers’ purpose, pedagogy, and philosophy emerged in the dialogic patterns of the online space. Practice was shaped by the lecturers’ epistemological positioning and their cultural values and beliefs. The practice, which was observed across different modules, reflected the different positions lecturers took when they approached online teaching. The research highlights the way in which a lecturers’ purpose, pedagogy, and philosophy are reflected in their online facilitation.